One Size Fits All? Reflecting on Local Program Planning Processes Among Three Iterations of the “Clemente” Program - Janet Groen; Tara Hyland-Russell (Adult Education Research Conference, 2007)
This paper reports on the first stage of an ongoing research project: how three Canadian adult education programs, which share the common mission of providing access to the study of the liberal arts for non-traditional adult learners, have evolved over the past few years. We consider both the commonalities and variances across the programs to understand how each iteration’s socio-political context has informed their interpretation of the common mission.